2018
DOI: 10.4026/isguc.466669
|View full text |Cite
|
Sign up to set email alerts
|

Algilanan Örgütsel Destek, Psi̇koloji̇k İyi̇ Oluş Ve İşten Ayrilma Ni̇yeti̇ Arasindaki̇ İli̇şki̇leri̇n Değerlendi̇ri̇lmesi̇

Abstract: Bu araştırmanın örneklemi 62 kadın, 50 erkek banka çalışanından oluşmaktadır. Bankacılık sektöründe çalışanlar arasında algılanan örgütsel destek, psikolojik iyi oluş ve işten ayrılma niyeti arasındaki ilişki araştırılmıştır. Algılanan örgütsel destek ile işten ayrılma niyeti arasında negatif; algılanan örgütsel destek ile psikolojik iyi oluş arasında pozitif anlamlı ilişkiler tespit edilmiştir. Psikolojik iyi oluş ile işten ayrılma niyeti arasında ise, anlamlı bir ilişki bulunamamıştır. Ayrıca katılımcıların … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…In large hotel businesses, hierarchical management structures and close monitoring of employees by authorities can foster abusive management practices and exacerbate work alienation. These findings are consistent with previous research (Aryee et al, 2016;Afsar & Badir, 2016;Bağdoğan, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In large hotel businesses, hierarchical management structures and close monitoring of employees by authorities can foster abusive management practices and exacerbate work alienation. These findings are consistent with previous research (Aryee et al, 2016;Afsar & Badir, 2016;Bağdoğan, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…Searle et al (2001) reported significant associations between perceived organizational support and individuals' self-confidence, job satisfaction, and work performance.However, the level of perceived organizational support significantly influences employees' intentions to leave the organization. Bağdoğan (2018) found that heightened perceived organizational support correlates with improved psychological wellbeing and a reduced intention to quit. Conversely, Chiu et al (2009) established a notable negative relationship between employees' perceived organizational support and their intention to quit.…”
Section: 2perceived Organizational Supportmentioning
confidence: 98%